Murder as violent extremism - Gruenewald, Jeff (Routledge handbook of homicide studies, 2024)
Empirical research on murder in the form of violent extremism, whether motivated by anti-government sentiment or discrimination of “others,” has increased over the last 15 years. This chapter covers extant literature that has studied violent extremism and in particular, as it relates to murder. This includes introductions to major categories of violent extremism and the similarities/differences between the categories. Unique to this line of study is the lack of reliable law enforcement data, leading to the development of open-source datasets. These methodological advancements in data collection are introduced along with research findings. Lastly, the chapter concludes with potential research opportunities that will further expand on what is known concerning murder and violent extremism.